The Inclination Towards Mutual Funds Investment in Today’s Youth - Shubhangi Gore; Alfiya Sajid Khan; Achal Ingle (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
People can participate in the investment process and generate income by placing their money in a variety of physical and financial assets. Because life is uncertain and the future cannot be predicted, one must invest in order to protect their future. Among other things, investors put money into the market with the hopes of making money, feeling secure, and appreciating their investments. A young investor has a wide range of investment options because, up until the age of 40, he will be able to generate a respectable return on his investment and has a reasonable risk tolerance and time horizon. Numerous investing possibilities are available, such as bank deposits, the equity market, mutual funds, and other financial instruments real estate, post office deposits, and actual gold. The study's major objective is to identify the preferences of young investors—those who are between the ages of 21 and 35—in the contemporary setting. The sentiments of the investors can vary from person to person even within the same age range. The researchers have looked into the various preferences among young investors using an easy-to-complete questionnaire and direct contact with the investors.